BIOLOGICAL DIVERSITY AND SYSTEM OF EDUCATION FOR SUSTAINABLE DEVELOPMENT ILLUSTRATED BY THE EXAMPLE OF EDUCATIONAL INSTITUTIONS OF KIZILYURT CITY - Zh. M.-S. Aliyeva; N. O. Guseynova; D. I. Kadieva; R. Kh. Gayrabekova (Юг России: экология, развитие)
Aim. The aim is to study the impact of environmental education on the quality of learning biology and ecology by the example of secondary schools in Kizilyurt city, Republic of Dagestan.Materials and methods. As a material for the research, we used the findings obtained in the survey and testing of students of 5-11 grades and teachers of Kizilyurt, developed at the Institute of Ecology and Sustainable Development of the Dagestan State University. Data processing was based on the general principles of statistics and was carried out using Statistica and Excel softwares.Results. By comparing the survey results of the students, we can draw conclusions about the quality of environmental education in particular schools. The results in general show some shortcomings in the planning and content of school curricula. Studies conducted in Kizilyurt schools demonstrate that environmental knowledge of the students is poor and primarily the acquisition occurs through the study of biology and a minor extent of geography.Conclusion. The analysis of ecological education of students of Kizilyurt schools based on national educational standards is an attempt to explain the real situation and to make recommendations to improve the system and content of the training in the field of education for sustainable development.